2012
DOI: 10.4081/reumatismo.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

The role of illness perception and emotions on quality of life in fibromyalgia compared with other chronic pain conditions

Abstract: Our study highlighted dysfunctional IP, low QoL, high EAV scores in FM patients and the significant relations between these variables. Research results provided support for relevance of a multidisciplinary approach to the management of FM, including psychological interventions, according to a biopsychosocial perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…This finding reflects the well-accepted idea that the experience of pain may respond to cultural rules and expectations (Lautenbacher & Fillingim, 2004;Melzack & Casey, 1962). Another study result, showing that more experiences of pain described in terms of emotional categories had lower estimates of quality of life, could be consistent with the knowledge that comes from research in cognitive psychology indicating the modifying influence of emotional pain on the perception of quality of life (Capraro et al, 2012). Chronicisation of pain suggests that pain experienced by patients is, generally, less intense than in the case of acute pain; however, when pain is chronic, anxiety or fear can transform into frustration, while sadness and low mood can transform into depression.…”
Section: Discussionsupporting
confidence: 81%
“…This finding reflects the well-accepted idea that the experience of pain may respond to cultural rules and expectations (Lautenbacher & Fillingim, 2004;Melzack & Casey, 1962). Another study result, showing that more experiences of pain described in terms of emotional categories had lower estimates of quality of life, could be consistent with the knowledge that comes from research in cognitive psychology indicating the modifying influence of emotional pain on the perception of quality of life (Capraro et al, 2012). Chronicisation of pain suggests that pain experienced by patients is, generally, less intense than in the case of acute pain; however, when pain is chronic, anxiety or fear can transform into frustration, while sadness and low mood can transform into depression.…”
Section: Discussionsupporting
confidence: 81%
“…Given a high proportion of people diagnosed with FM are women (Yunus et al, 2000 ), understanding the unique experiences of women who have FM is important to improve health outcomes, as has previously been done in other female-based FM studies (Capraro et al, 2012 ; McInnis et al, 2014 ; Stuifbergen et al, 2006 ). Consistent with past research, this study observed that an increase in FM severity was associated with more negative illness perceptions (Stuifbergen et al, 2006 ; Van Wilgen et al, 2008 ), higher pain catastrophizing (Lami et al, 2018 ), lower pain acceptance (Lami et al, 2018 ; Rodero et al, 2011 ), poorer QoL, and higher psychological distress (De Souza Santos Berber et al, 2005 ; Lee et al, 2017 ; Schaefer et al, 2011 ; Toussaint et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fibromyalgia (FM) is a painful medical condition associated with poor treatment outcomes and quality of life (QoL) (Arnold et al, 2011 ; Choy et al, 2010 ; Clark et al, 2013 ; Skaer & Kwong, 2017 ). Compared to other pain-related illnesses, autoimmune disorders, and the general public, individuals with FM report higher psychological distress (Capraro et al, 2012 ; Lami et al, 2018 ; McInnis et al, 2014 ; Schaefer et al, 2016 ; Toussaint et al, 2019 ). Additionally, higher FM symptoms have been shown to relate to greater psychological distress (PD) and poorer QoL (De Souza Santos Berber et al, 2005 ; Lee et al, 2017 ; Schaefer et al, 2011 ; Toussaint et al, 2017 ).…”
mentioning
confidence: 99%
“…Research has shown that in the case of FM, there is a higher incidence of depressive symptomatology, a stronger impairment of quality of life, and worst illness perception [19]. Individuals with FM are three times more likely to experience depressive symptoms than the general population [20], with 90% of patients displaying depressive symptoms and 62% receiving a diagnosis of major depression over the course of their illness [21].…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores indicate more severe depression symptoms. The cut-off points for the BDI symptoms are as follows: minimal (0-13), mild (14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe (29-63; [28]). In the current study, the internal consistency coefficient was α = 0:84.…”
mentioning
confidence: 99%